COMPARATIVE EVALUATION OF RAPID DIAGNOSTIC MODALITIES AND PROGNOSTIC BIOMARKERS IN ICU SEPSIS PATIENTS: A RETROSPECTIVE COHORT STUDY ON DIAGNOSTIC EFFICIENCY, BIOMARKER PERFORMANCE, AND SURVIVAL OUTCOMES - DEEPAK ARKALGUD; ASHOK PAL GOBIND; SARIDE NAVEEN KUMAR; PANNEERSELVAM PERIASAMY; ARBIND KUMAR CHOUDHARY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Researchers evaluated two objectives of this study: They compared modern molecular testing methods against standard blood cultures for pathogen identification in intensive care unit (ICU) sepsis patients. The study evaluated the prognostic value of biomarkers interleukin-6 (IL-6) and procalcitonin and C-reactive protein and lactate. Methods: The research analyzed 275 adult sepsis patients at a tertiary care teaching hospital who received care in their ICU. The study divided participants according to their diagnostic testing approach. The researchers evaluated clinical parameters and biomarker levels, diagnosis timing, antimicrobial initiation, and patient outcomes through analysis of variance and logistic regression, Cox proportional hazards models, Kaplan–Meier survival analysis, and receiver operating characteristic curve analysis. Results: Rapid diagnostic instruments enabled pathogen detection in a more timely fashion at which healthcare providers started proper antibiotic treatment (p<0.001). Patients who received their diagnosis through Microfluidics point-of-care and Multiplex polymerase chain reaction testing spent less time in both ICU and hospital facilities. The mortality rates between groups remained similar but elevated IL-6 and lactate levels strongly indicated poor clinical outcomes while IL-6 proved most effective for outcome prediction (area under the curve=0.85). The mortality risk decreased by 53% when antibiotics were administered early (p=0.001). None of the biomarkers proved reliable for predicting ICU stay duration. Conclusion: Early detection of sepsis becomes more accurate when combined molecular diagnostics work with biomarker quantification for enhanced treatment accuracy. The combination of IL-6 and lactate proves to be a powerful indicator of negative clinical results. These research findings confirm the strategic value of fast diagnostics combined with biomarker risk evaluation for sepsis protocols at all levels of medical resource availability.